2011
DOI: 10.3892/etm.2011.293
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-dependent cytotoxic synergism of pemetrexed and erlotinib in BXPC-3 and PANC-1 human pancreatic cancer cells

Abstract: Abstract. Previous studies have shown that both pemetrexed, a cytotoxic drug, and erlotinib, an epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), inhibit the cell growth of pancreatic cancer cells. However, whether they exert a synergistic antitumor effect on pancreatic cancer cells remains unknown. The present study aimed to assess the synergistic effect of erlotinib in combination with pemetrexed using different sequential administration schedules on the proliferation of human pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Since AREG binds either EGFR homodimer (EGFR/EGFR) or EGFR/ERBB2 heterodimer, EGFR specific inhibitors may be effective for PDACs' treatment if escaping the stroma barrier in vivo . In this subject, Wang L et al 22 demonstrated that Erlotinib, an EGFR specific chemical inhibitor, showed marked anti-cancer functions in BxPC3 cells, which possess no mutation of EGFR. In addition, Larbouret C et al 23 found that targeting approach to EGFR/HER2 heterodimer on PDACs using the combination of Cetuximab (therapeutic anti-EGFR antibody) with Trastuzumab (therapeutic anti-HER2 antibody) produced remarkable tumor suppressing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since AREG binds either EGFR homodimer (EGFR/EGFR) or EGFR/ERBB2 heterodimer, EGFR specific inhibitors may be effective for PDACs' treatment if escaping the stroma barrier in vivo . In this subject, Wang L et al 22 demonstrated that Erlotinib, an EGFR specific chemical inhibitor, showed marked anti-cancer functions in BxPC3 cells, which possess no mutation of EGFR. In addition, Larbouret C et al 23 found that targeting approach to EGFR/HER2 heterodimer on PDACs using the combination of Cetuximab (therapeutic anti-EGFR antibody) with Trastuzumab (therapeutic anti-HER2 antibody) produced remarkable tumor suppressing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Considering some previously published results such as X. Yu et al (IC 50 = 0.2 μM to gemcitabine in BxPC3 cell line) [30], A. Singh et al (IC 50 = 123.9 μM to gemcitabine in PANC-1 cell line) [31], A. Acuna et al (IC 50 = 46.5 μM to PH-427 in BxPC3 cell line) [32], S. Mukai et al (IC 50 = 19.5 μM and 20.4 μM to gefitinib in BxPC3 and PANC-1 cell lines, respectively) [33], L. Wang et al (IC 50 = 39.86 μM and 83.76 μM to Pemetrexed in BxPC3 and PANC-1 cell lines, respectively) [34] or even A. Wright et al (IC 50 = 70.9 μM and 22.8 μM to Aphrocallistin in BxPC3 and PANC-1 cell lines, respectively) [35], we can suggest that Parvifloron D has a higher cytotoxic potential (IC 50 = 0.15 ± 0.05) to these pancreatic tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…EGFR is the cell surface tyrosine kinase receptor, and activated EGFR recruits and phosphorylates cytoplasmic signalling molecules, thus initiating downstream signalling cascades including JAK/STATs, MAPK/ERK, and PI3K/AKT, to promote tumour cell proliferation, invasion and distant metastasis (Hynes & Lane, 2005; Wang et al., 2011a; Wang, Zhu, Zhang, & Zhang, 2011). However, despite the intersection of signalling activation in different tumours, there may be a preference for EGFR‐activated signalling transduction for the metastasis of tumour cells.…”
Section: Discussionmentioning
confidence: 99%